A comprehensive review of nucleic acid-based methods for disease diagnosis, treatment, & prevention - Al-Muzafar, Hessah Mohammed (International Journal of Innovative Research and Scientific Studies, 2025)
Nucleic acid-based technologies have revolutionized the diagnosis, treatment, and prevention of diseases by enabling highly sensitive and specific detection of genetic material from both pathogens and host cells. These molecular approaches have proven particularly critical in the early detection and surveillance of infectious diseases. For instance, during the outbreak of swine-origin influenza A (H1N1) in Mexico, nucleic acid-based diagnostics were quickly deployed to detect and subtype the virus, and efforts intensified to develop low-cost, point-of-care tests. Such technologies also hold potential for monitoring antiviral resistance mutations and tracking genomic reassortment events with highly pathogenic strains, such as avian influenza. This review provides a comprehensive overview of key nucleic acid amplification techniques—including polymerase chain reaction (PCR), loop-mediated isothermal amplification (LAMP), and transcription-mediated amplification (TMA)—with a focus on their principles, advantages, and limitations. Applications across diverse areas such as infectious disease diagnostics, cancer screening, and genetic disorder detection are discussed, with emphasis on tools like circulating tumor DNA (ctDNA), DNA methylation markers, and gene mutation profiling. Furthermore, the therapeutic potential of nucleic acid-based strategies, including gene editing (e.g., CRISPR-Cas systems) and RNA interference, is explored. Finally, the review addresses ongoing challenges, such as sample preparation, assay standardization, and integration into point-of-care platforms, alongside emerging trends that promise to enhance the future of molecular diagnostics.